(untitled) (Computer-Assisted Language Learning Electronic Journal, 2024)
Online chat applications have become increasingly popular with the new generation of L2 learners. These new technologies are used for entertainment as well as communication. In spite of incremental pragmatic studies devoted specifically to analyze requests, little is known about L2 learners’ requests to faculty in instant text-based communication. As L2 learners lack a clear instruction for mitigating their requests in instant text- based communication like WhatsApp, the present study aimed to examine the pragmalinguistic features of graduate students’ requests to faculty on WhatsApp. Furthermore, attempts have been made to determine the writing features of graduate students’ requests. The data were a natural corpus of 196 requests written by Iranian graduate students to their professor on WhatsApp, which were coded and analyzed qualitatively. Findings suggest that conventionally indirect strategies were the most prominent request strategies favored by graduate students. Analysis of alerters indicated that the participants mostly used formal address terms. Furthermore, external and internal modifiers were combined in the participants’ requests. Analyses of their writing features revealed that the participants tended to use short sentences. In addition, the quality of punctuation and capitalization was relatively poor. Findings bear pedagogical implications for L2 learners, teachers, and course designers.